Organizational hierarchies and export destinations - Irene Brambilla; Andrés César; Guillermo Falcone; Guido G. Porto (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
This paper proposes a new link relating export destinations and the organization of the firm. We claim that the production of higher-quality varieties exported to rich destinations induces firms to re-structure their production processes, becoming organizationally more complex. We introduce a theoretical model with these features and we explore the mechanisms using a panel of Chilean manufacturing plants. Our identification strategy relies on falling tariffs on Chilean products across destinations caused by the signature of Free Trade Agreements with high-income countries (the European Union, the United States, and South Korea). We find that Chilean plants that were induced by these tariff reductions to start exporting to high-income destinations increased the number of hierarchical layers and upgraded the quality of their products. This involved the addition of qualified supervisors that facilitated the provision of higher product quality. These effects took place at new high-income exporting firms.
Keywords: F14; F16; J24; 330; Exports; Export destinations; Organizational change; Quality